Conductive shielding material for high-voltage cable and preparation method of conductive shielding material
By modifying conductive carbon black and cross-linking network structure, the problems of conductive network stability and interface compatibility of conductive shielding materials for high-voltage cables under high temperature and high current carrying conditions were solved, achieving high conductivity and long-term reliability of the material.
Patent Information
- Application Number
- CN202511416176.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-29
- Publication Date
- 2025-12-12
AI Technical Summary
Existing conductive shielding materials for high-voltage cables exhibit poor stability of the conductive network structure under high-temperature and high-current conditions. They are prone to a sharp increase in resistivity due to thermal expansion and lack compatibility with the insulation layer, affecting the long-term operational reliability and safety of the cable.
A dual crosslinking network structure was constructed using surface-modified conductive carbon black, peroxide crosslinking agent, and functionalized silane coupling agent. The dispersibility of conductive carbon black in the polymer matrix was improved by plasma oxidation, solution grafting polymerization, and surface coupling agent treatment. Furthermore, the interfacial compatibility was enhanced by grafting polyolefin with maleic anhydride.
This method achieves uniform dispersion of conductive carbon black in the polymer matrix, improves the structural stability and interfacial compatibility of the conductive network, reduces resistivity rise, and ensures safe operation and long-term reliability of the cable under high temperature and high current carrying conditions.
Smart Images

Figure CN121108613A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a conductive shielding material for high-voltage cables and its preparation method. Background Technology
[0002] High-voltage cables are crucial in modern power transmission. With their strong long-distance transmission capacity, high current carrying capacity, and low loss, they have become the core of key infrastructure projects such as urban power transmission, cross-river channels, and deep-sea power transmission. The semi-conductive shielding layer in their structure, tightly fitted to the inner and outer interfaces of the main insulation layer, eliminates minute defects caused by manufacturing or operation between the metal conductor and the insulating material, achieving uniform distribution of the interface electric field and fundamentally suppressing partial discharge.
[0003] Conductive shielding materials for high-voltage cables on the market are mainly prepared by melt blending and compounding high-molecular matrix resins, highly active conductive carbon black, and various processing aids. Conductive carbon black, as the core functional component, directly determines the overall electrical and mechanical properties of the semi-conductive shielding material through its quality and dispersion state in the base resin. However, due to its nano-sized particle size, large specific surface area, and high surface energy, conductive carbon black is thermodynamically unstable and easily attracts and agglomerates, forming large agglomerates with numerous weak internal interfaces. This hinders the construction of an efficient conductive network within the material, weakens the conductivity of the shielding material, affects macroscopic mechanical properties, and can also form protrusions on the surface of the product, damaging its smoothness and posing a potential risk to the uniformity of the local electric field during cable operation. Existing technologies attempt to introduce large amounts of dispersants to improve its dispersion state, but this leads to new problems: excessive dispersants form an insulating coating layer on the surface of the conductive carbon black, reducing the overall conductivity of the shielding material, increasing the complexity of the production process and manufacturing costs, and decreasing its economic efficiency and practicality.
[0004] With the growth of global electricity demand, the current-carrying capacity of high-voltage transmission systems is increasing, making the maximum operating temperature of high-voltage cables closely related to their current-carrying capacity. Under harsh high-temperature operating environments, the volume expansion effect of existing semi-conductive shielding materials has become a prominent technical challenge. Thermal expansion can damage the continuous conductive network constructed by the conductive filler. When the temperature approaches the melting point of the matrix resin, the structural damage to the conductive network reaches a critical level, leading to a sharp increase in material resistivity and threatening the normal operation of the cable. Current technologies addressing conductivity issues focus on forming conductive pathways, but neglect their structural stability over a wide temperature range, especially their resistance to thermal expansion of the matrix resin. This results in even good initial dispersion, internal stress at high temperatures tearing apart the conductive pathways. Furthermore, the high-sealing structure of high-voltage cables means that their internal heat dissipation capacity is far lower than the rate of heat accumulation. Heat accumulates in the insulation layer, causing significant adverse changes in the electrical and thermal properties of the semi-conductive layer and the insulation layer, challenging the overall safe operation of the cable. For example, some semiconductive shielding materials using ethylene-vinyl acetate copolymer (EVA) as the matrix resin are prone to conductive network damage at high temperatures. Furthermore, EVA has poor compatibility with cable insulation materials, easily leading to interface delamination and preventing the formation of a stable integrated structure, thus affecting the long-term reliability of the cable. While ethylene-acrylic acid resin (EAA) boasts excellent performance, its high cost limits its widespread application, making it difficult to balance economy and performance. Therefore, existing technologies, while achieving conductivity, struggle to overcome issues such as insufficient dispersion of conductive fillers and poor structural stability of the conductive network under high-temperature, high-current conditions, and also fail to balance performance, cost, and material compatibility. Summary of the Invention
[0005] (a) Technical problems to be solved
[0006] To address the shortcomings of existing technologies, this invention provides a conductive shielding material for high-voltage cables and its preparation method, solving the problem of "unsatisfactory performance" in the aforementioned background technologies.
[0007] (II) Technical Solution
[0008] To achieve the above objectives, the present invention provides the following technical solution: a conductive shielding material for high-voltage cables, comprising the following components by weight:
[0009] The composition includes 40 to 70 parts of a main polyolefin resin, 10 to 30 parts of an ethylene-vinyl acetate copolymer, 5 to 15 parts of maleic anhydride-grafted polyolefin, 20 to 40 parts of surface-modified conductive carbon black, 0.5 to 2 parts of a peroxide crosslinking agent, 0.5 to 3 parts of a functionalized silane coupling agent, 0.1 to 1 part of a processing aid, and 0.1 to 1 part of an antioxidant.
[0010] The surface-modified conductive carbon black is a high-structure conductive carbon black that has undergone plasma oxidation treatment, solution graft polymerization and surface coupling agent pretreatment, with an oil absorption value of 150mL / 100g to 300mL / 100g and a particle size distribution of 20nm to 60nm.
[0011] The peroxide crosslinking agent and the functionalized silane coupling agent form a dual crosslinking network structure, wherein the peroxide crosslinking agent initiates the formation of a three-dimensional organic polymer network in the polymer matrix, and the functionalized silane coupling agent forms an inorganic-organic hybrid siloxane network.
[0012] Preferably, the main polyolefin resin is low-density polyethylene, linear low-density polyethylene, or a mixture thereof in any proportion, with a density of 0.910 g / cm³. 3 Up to 0.930 g / cm 3 The melt flow rate (190°C / 2.16kg) is 0.5g / 10min to 5g / 10min.
[0013] Preferably, the ethylene-vinyl acetate copolymer contains 18% to 28% vinyl acetate by mass.
[0014] Preferably, the maleic anhydride-grafted polyolefin is selected from maleic anhydride-grafted polyethylene or maleic anhydride-grafted linear low-density polyethylene, and the grafting rate of maleic anhydride is 0.5% to 2.0% by mass.
[0015] Preferably, the plasma oxidation treatment of the surface-modified conductive carbon black is carried out in a low-pressure gas environment, with the atmosphere being pure oxygen, air, or a mixture of nitrogen and oxygen in a volume ratio of 4:1. The radio frequency power is 50W to 500W, and the treatment time is 10 minutes to 60 minutes. The solution graft polymerization involves grafting a low molecular weight polyolefin onto the surface of the conductive carbon black under the action of a free radical initiator. The molecular weight of the low molecular weight polyolefin is 5000 to 10000 g / mol. The reaction temperature is 80°C to 150°C, and the reaction time is 4 hours to 8 hours. The surface coupling agent pretreatment uses a silane coupling agent or a titanate coupling agent, reacting at 50°C to 70°C for 2 hours to 4 hours, followed by vacuum drying at 80°C to 120°C for 12 hours to 24 hours.
[0016] Preferably, the peroxide crosslinking agent is selected from one or more of dicumyl peroxide, di-tert-butyl peroxide, or 2,5-dimethyl-2,5-di-tert-butylperoxyhexane.
[0017] Preferably, the functionalized silane coupling agent is selected from one or more of vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, or N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
[0018] Preferably, the processing aid is selected from one or more of fatty acids and their derivatives, polyethylene wax or paraffin oil; the antioxidant is selected from one or more of hindered phenolic antioxidants, phosphite antioxidants or thioester antioxidants.
[0019] Preferably, a method for preparing a conductive shielding material for high-voltage cables includes the following steps:
[0020] S1: Surface-modified conductive carbon black was prepared by plasma oxidation treatment, solution graft polymerization and surface coupling agent pretreatment to modify the high-structure conductive carbon black;
[0021] S2: Premixing: The main polyolefin resin, ethylene-vinyl acetate copolymer, maleic anhydride grafted polyolefin, surface-modified conductive carbon black prepared in step S1, processing aids and antioxidants are added into a high-speed mixer in proportion and mixed at 500 rpm to 1500 rpm for 5 to 15 minutes, while controlling the temperature to ≤80°C.
[0022] S3: Melt blending, the premixed material is fed into a twin-screw extruder with an aspect ratio of 36 to 52, the screw speed is 100 rpm to 300 rpm, and the temperatures of each section are: feed zone 140°C to 160°C, melt zone 160°C to 180°C, mixing and shearing zone 180°C to 200°C, metering zone 170°C to 190°C, and die zone 170°C to 190°C; the peroxide crosslinking agent and the functionalized silane coupling agent are added before the metering zone through the side feed port;
[0023] S4: Cooling and granulation, extruding the molten blend into strips, cooling and then pelletizing.
[0024] Preferably, the mixing and shearing zone of the twin-screw extruder in S3 is equipped with a kneading block, a mixing disc, and a reverse conveying section to provide high shear force; the extruder is equipped with a vacuum exhaust port to remove volatile substances.
[0025] (III) Beneficial Effects
[0026] This invention provides a conductive shielding material for high-voltage cables and its preparation method. It has the following beneficial effects:
[0027] (1) This invention effectively solves the problem of agglomeration caused by high surface energy of conductive carbon black by multi-step surface modification of conductive carbon black through plasma oxidation, solution graft polymerization and surface coupling agent pretreatment, and in situ chemical bonding of maleic anhydride grafted polyolefin. It achieves uniform dispersion of conductive carbon black in polymer matrix without the need for excessive dispersant, which avoids the decrease in conductivity caused by the insulating coating of dispersant, simplifies the production process, reduces manufacturing cost, and takes into account the conductivity, mechanical properties and surface smoothness of the material.
[0028] (2) This invention utilizes the organic polymer three-dimensional network formed by the peroxide crosslinking agent and the inorganic-organic hybrid siloxane network formed by the functionalized silane coupling agent to construct a double crosslinking structure. The siloxane network can effectively limit the relative displacement of conductive carbon black at high temperature, resist the damage of the conductive network to the polymer matrix by thermal expansion, improve the structural stability of the conductive network in a wide temperature range, solve the problem of the resistivity of existing materials rising sharply due to thermal expansion under high temperature and high current conditions, and ensure the safe operation of the cable.
[0029] (3) This invention improves the interfacial compatibility and adhesion between the semiconductive shielding layer and the insulation layer by the interaction between the polar groups of maleic anhydride-grafted polyolefin and the cable insulation layer (such as XLPE), as well as the synergistic effect between the main polyolefin resin and the ethylene-vinyl acetate copolymer, effectively preventing interfacial peeling. At the same time, it selects cost-effective polyolefin and EVA as the matrix, avoiding the use of high-cost resins (such as EAA), thus balancing performance and economy while improving the long-term operational reliability of the material. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of a preferred modification method for surface-modified conductive carbon black according to the present invention;
[0031] Figure 2 This is a schematic diagram of the process for preparing conductive shielding material for high-voltage cables according to the present invention. Detailed Implementation
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Please see Figure 1 - Figure 2 This invention provides a conductive shielding material for high-voltage cables. The conductive shielding material comprises (by weight parts) a main polyolefin resin, ethylene-vinyl acetate copolymer, maleic anhydride-grafted polyolefin, surface-modified conductive carbon black, peroxide crosslinking agent, functionalized silane coupling agent, processing aid, and antioxidant. Specifically:
[0034] The content of the main polyolefin resin ranges from 40 to 70 parts. The main polyolefin resin serves as the basic polymer backbone of the conductive shielding material. Specifically, the main polyolefin resin is preferably low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), or a mixture thereof in any proportion. Low-density polyethylene possesses excellent melt processing properties and good flexibility due to its branched structure, while linear low-density polyethylene, with its more regular molecular chain structure and higher crystallinity, provides the material with higher tensile strength, puncture resistance, and resistance to environmental stress cracking. By adjusting the mixing ratio of these two polyethylenes, a precise balance can be achieved between the material's processing fluidity and final mechanical properties. Furthermore, the density of the main polyolefin resin is strictly controlled at 0.910 g / cm³. 3 Up to 0.930 g / cm 3 Within a certain range, appropriate physical density and crystallinity are ensured. Its melt flow rate (MFR, measured at 190°C / 2.16 kg) is limited to between 0.5 g / 10 min and 5 g / 10 min. This MFR range ensures good flowability of the polymer during melt blending and subsequent cable extrusion molding, effectively encapsulating and dispersing conductive carbon black, while avoiding extrusion difficulties due to excessive flowability or excessive shear heat and material degradation due to insufficient flowability.
[0035] The content of ethylene-vinyl acetate copolymer ranges from 10 to 30 parts. Ethylene-vinyl acetate copolymer is an important material for improving the flexibility, elasticity, and key interfacial properties of conductive shielding materials. Ethylene-vinyl acetate copolymer (EVA) introduces polar vinyl acetate (VA) units into its polyethylene backbone, with a vinyl acetate mass percentage of 18% to 28%. The polarity of the vinyl acetate units improves the wetting properties of the polymer matrix for high surface energy conductive carbon black, thereby assisting in the initial dispersion of conductive carbon black during melt blending and reducing the tendency for carbon black agglomeration. Furthermore, the introduction of vinyl acetate units imparts higher flexibility to the polymer chain, thereby improving the low-temperature toughness and elasticity of the conductive shielding material. The presence of ethylene-vinyl acetate copolymer also improves the melt viscosity of the polymer matrix to some extent, further optimizing processing performance.
[0036] The content of maleic anhydride-grafted polyolefin ranges from 5 to 15 parts. Specifically, the maleic anhydride-grafted polyolefin (MA-g-PO) can be selected from maleic anhydride-grafted polyethylene (MA-g-PE) or maleic anhydride-grafted linear low-density polyethylene (MA-g-LLDPE), with the grafting rate of maleic anhydride strictly controlled between 0.5% and 2.0% (mass percentage). Maleic anhydride groups possess high chemical reactivity. During melt blending, these grafted maleic anhydride groups can undergo in-situ chemical bonding reactions with specific functional groups (e.g., hydroxyl, carboxyl, and amino groups) pre-introduced on the surface of surface-modified conductive carbon black, such as esterification or amidation reactions. Through this robust covalent bonding, the conductive carbon black nanoparticles are firmly "anchored" within the polymer matrix, thereby inhibiting the agglomeration and re-agglomeration of carbon black particles in the melt at the molecular level, greatly improving the dispersion uniformity of conductive carbon black in the polymer matrix. Uniformly dispersed conductive carbon black constructs a highly efficient and continuous conductive network, thereby reducing the volume resistivity of the material and ensuring excellent surface finish. Furthermore, the polar maleic anhydride groups on the maleic anhydride-grafted polyolefin molecular chains can effectively physical entangle or chemically interact with the polar groups or residual initiator decomposition products in the high-voltage cable insulation layer (typically cross-linked polyethylene XLPE). This significantly improves the interfacial compatibility and adhesion between the semi-conductive shielding layer and the insulation layer, effectively preventing interfacial peeling caused by thermal cycling or mechanical stress during long-term operation of the high-voltage cable, ensuring the overall structural integrity and operational reliability of the cable.
[0037] The content of surface-modified conductive carbon black ranges from 20 to 40 parts, with high-structure conductive carbon black being preferred. Its oil absorption value (DBP absorption value) is controlled between 150 mL / 100 g and 300 mL / 100 g. Due to its inherent three-dimensional branched structure, high-structure carbon black can form a conductive network at relatively low addition levels, thereby maintaining conductivity while reducing adverse effects on the material's mechanical properties. The surface of the conductive carbon black is functionalized using precise physical or chemical methods. Specific modification methods include the following:
[0038] Step 1: Plasma oxidation treatment. By exciting plasma in a low-pressure gas environment, the surface of conductive carbon black comes into contact with active oxygen species, thereby introducing abundant oxygen-containing functional groups, such as hydroxyl (-OH), carboxyl (-COOH), and carbonyl (-C=O), onto its surface. These oxygen-containing functional groups not only enhance the hydrophilicity of the conductive carbon black and its polar interaction with the polymer matrix, but more importantly, they provide active sites for subsequent reactions with maleic anhydride-grafted polyolefins, promoting the formation of in-situ chemical bonds.
[0039] Step 2: Solution graft polymerization, which mainly involves covalently grafting low molecular weight polyolefins (such as low molecular weight polyethylene or polypropylene) onto the surface of conductive carbon black through free radical polymerization or catalytic polymerization. This "polymer brush" layer formed on the carbon black surface has a chemical structure highly similar to the host polyolefin matrix. This reduces the surface energy of the conductive carbon black, improves its physical compatibility with the host polyolefin matrix, and promotes its uniform dispersion in the polymer melt, thereby constructing a more stable and efficient conductive network.
[0040] Step 3: Surface coupling agent pretreatment. The conductive carbon black surface is pretreated by using silane coupling agents (e.g., aminosilane, epoxysilane) or titanate coupling agents. The coupling agent molecules have dual reactivity: one end reacts with the carbon black surface to form a stable bond, and the other end contains functional groups that are compatible with or reactive with the polymer matrix.
[0041] Furthermore, the particle size distribution of the surface-modified conductive carbon black is controlled within the range of 20nm to 60nm, ensuring that excessively large carbon black agglomerates are avoided while maintaining high conductivity, thereby further guaranteeing the surface smoothness and uniformity of the electric field distribution of the material.
[0042] The content of the peroxide crosslinking agent ranges from 0.5 to 2 parts. The peroxide crosslinking agent decomposes at high temperatures to generate free radicals, which are key components in constructing the organic three-dimensional network structure of the conductive shielding material. The peroxide crosslinking agent can be selected from one or more of dicumyl peroxide (DCP), di-tert-butyl peroxide (DTBP), or 2,5-dimethyl-2,5-di-tert-butylperoxyhexane (DHBP). These peroxides can decompose at specific temperatures to generate highly reactive free radicals. These free radicals can abstract hydrogen atoms from the main polyolefin resin, ethylene-vinyl acetate copolymer, and maleic anhydride-grafted polyolefin molecular chains, thereby forming carbon-carbon (CC) covalent bonds between the polymer molecular chains. In this way, the originally independent polymer molecular chains are linked together to construct a stable three-dimensional network crosslinked structure. The formation of the crosslinked structure significantly improves the heat deformation resistance, high-temperature mechanical strength, creep resistance, and dimensional stability of the conductive shielding material. This reinforced polymer matrix provides a fundamental and solid support for the structural stability of the internal conductive carbon black network under high-temperature and high-current-carrying conditions.
[0043] The content of the functionalized silane coupling agent ranges from 0.5 parts to 3 parts. The functionalized silane coupling agent can be selected from one or more of vinyltrimethoxysilane (VTMS), γ-aminopropyltriethoxysilane (APTES), or N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane (EDA-APTES). The main functions of the functionalized silane coupling agent include the following:
[0044] 1. Functionalized silane coupling agents have reactive functional groups, such as vinyl and amino groups, at one end of their molecules. These functional groups can chemically bond with the molecular chains of the polymer matrix (especially the vinyl groups in vinyltrimethoxysilane, which can crosslink with polyolefins via free radical reactions) or with the functional groups on the surface of surface-modified conductive carbon black during melt blending or subsequent crosslinking and curing.
[0045] 2. Functionalized silane coupling agents contain a hydrolyzable alkoxysilane group (e.g., methoxy or ethoxy) at the other end of their molecules. In the presence of water vapor and under high temperature conditions, the alkoxysilane group can undergo a hydrolysis reaction to generate highly reactive silanol groups (-Si-OH). Subsequently, these silanol groups undergo a condensation reaction at high temperature to dehydrate and form stable siloxane (Si-O-Si) bonds.
[0046] The peroxide crosslinking agent initiates a free radical crosslinking reaction in the polymer matrix at high temperatures, forming a three-dimensional organic polymer network. This three-dimensional organic polymer network, together with the inorganic-organic hybrid siloxane network formed by the functionalized silane coupling agent, creates a unique double-crosslinked network structure. This double-crosslinked network structure is the core mechanism of this invention to combat the rapid increase in resistivity at high temperatures. The organic polymer network provides overall mechanical strength and resistance to heat deformation, while the siloxane network acts like a "molecular spring" and "molecular rivet," effectively limiting the relative displacement and rearrangement of the surface-modified conductive carbon black nanoparticles due to the volume expansion of the polymer matrix caused by thermal expansion, thanks to its unique elasticity and stability. The siloxane network maintains stable connections and the integrity of conductive pathways between conductive carbon black particles and between carbon black and the matrix, fundamentally preventing structural damage to conductive pathways at high temperatures. This significantly suppresses the rapid increase in material resistivity with temperature, ensuring the stable conductivity and operational reliability of the conductive shielding material for high-voltage cables under long-term, high-temperature, and high-current-carrying conditions.
[0047] The processing aid is present in a range of 0.1 to 1 part, and can be selected from one or more of fatty acids and their derivatives (e.g., stearic acid, zinc stearate, calcium stearate), polyethylene wax, or paraffin oil. These aids effectively reduce the viscosity of the polymer melt and improve flowability during melt blending by forming a lubricating layer or reducing intermolecular forces within the polymer melt. This not only helps achieve uniform dispersion of conductive carbon black at lower shear forces and reduces agglomerate formation, but also reduces energy consumption required for extrusion processing, improves production efficiency, and imparts excellent surface finish to the final product.
[0048] The antioxidant content ranges from 0.1 to 1 part, and the antioxidant can be selected from one or more of hindered phenolic antioxidants (e.g., IRGANOX 1010, IRGANOX 1076), phosphite antioxidants (e.g., IRGAFOS 168), or thioester antioxidants. These antioxidants effectively inhibit thermo-oxidative aging reactions that may occur in polymers during high-temperature processing (e.g., extrusion blending) and long-term operation (e.g., cables operating under high temperature and high pressure). By delaying polymer degradation, the antioxidant can maintain the molecular structural integrity of the material, thereby ensuring that the conductivity, mechanical properties, and interfacial adhesion properties of the conductive shielding material remain stable over a long service life.
[0049] Based on the above, the present invention also provides a method for preparing conductive shielding material for high-voltage cables, specifically including the following steps:
[0050] S1: Step 1: Preparation of surface-modified conductive carbon black, mainly to impart specific surface properties to the conductive carbon black in order to optimize its dispersibility and reactivity in the polymer matrix. The high-structure conductive carbon black is pretreated according to the preferred modification method described above.
[0051] Specifically, if plasma oxidation is used, conductive carbon black can be placed in a dedicated plasma reactor under a precisely controlled atmosphere (e.g., pure oxygen, air, or a mixture of nitrogen and oxygen in a 4:1 volume ratio) and a radio frequency power of 50W to 500W can be applied for a treatment time of 10 to 60 minutes. This process can directionally introduce oxygen-containing functional groups onto the carbon black surface, and their content can be quantitatively analyzed by X-ray photoelectron spectroscopy (XPS).
[0052] If solution graft polymerization is used, low molecular weight polyethylene (e.g., molecular weight 5000–10000 g / mol) must first be dissolved in a suitable solvent (e.g., toluene or xylene). Conductive carbon black is then dispersed in the solvent, and the reaction is carried out at a temperature of 80°C to 150°C for 4 to 8 hours under the action of a free radical initiator (e.g., benzoyl peroxide), allowing the polyethylene chains to be covalently grafted onto the carbon black surface. The grafting efficiency can be evaluated by thermogravimetric analysis (TGA).
[0053] If surface coupling agent pretreatment is used, conductive carbon black can be dispersed in an ethanol / water mixed solvent, and a specific concentration of aminosilane coupling agent (e.g., γ-aminopropyltriethoxysilane) can be added. The mixture is stirred at 50°C to 70°C for 2 to 4 hours, allowing the aminosilane to hydrolyze and condense on the carbon black surface to form a thin film. Subsequently, unreacted substances are removed by filtration and washing, and the carbon black is vacuum dried at 80°C to 120°C for 12 to 24 hours.
[0054] To further clarify, the modified conductive carbon black must undergo strict quality control. For example, its particle size and agglomeration state can be observed using transmission electron microscopy (TEM) or scanning electron microscopy (SEM), and the types and contents of its surface functional groups can be detected using Fourier transform infrared spectroscopy (FTIR) or X-ray photoelectron spectroscopy (XPS) to ensure that its modification effect and quality meet the requirements for subsequent blending.
[0055] S2: Premixing primarily involves the initial macroscopic uniform dispersion of all solid and liquid components, providing a uniform feed for subsequent melt blending. The main polyolefin resin, ethylene-vinyl acetate copolymer, maleic anhydride-grafted polyolefin, surface-modified conductive carbon black prepared in step one, processing aids, and antioxidants are weighed according to a pre-defined precise ratio. All weighings are performed using a high-precision electronic balance to ensure accurate proportions. The weighed materials are then fed into a high-speed mixer for initial mixing. The speed of the high-speed mixer is controlled within the range of 500 rpm to 1500 rpm, and the mixing time is 5 to 15 minutes. The frictional heat and shear force generated by the high-speed rotation achieve initial uniform dispersion of the components in a solid or semi-solid state. During this process, the temperature of the materials must be strictly monitored to avoid polymer degradation or damage to the conductive carbon black due to localized overheating. Typically, the internal temperature of the mixer should be controlled below 80°C to prevent any potential premature crosslinking or thermal degradation.
[0056] S3: Melt blending, primarily aimed at achieving complete polymer melting, ultrafine dispersion of conductive carbon black, and in-situ chemical reactions of key components. The premixed material from S2 is fed into a twin-screw extruder via a metering system for melt blending. The twin-screw extruder preferably has a high length-to-diameter ratio (L / D), ranging from 36 to 52, to provide sufficiently long mixing zones and residence times. The screw speed is controlled between 100 rpm and 300 rpm to balance shear force, material residence time, and production efficiency.
[0057] Furthermore, extruders are typically divided into multiple heating zones, each with optimized temperature settings:
[0058] The temperature of the feeding zone (first section) is set to 140℃ to 160℃ to preheat and initially plasticize the material and prevent it from sticking to the wall or bridging.
[0059] The temperature of the melting zone (second to third section) is set to 160°C to 180°C to ensure that the main polyolefin resin and ethylene-vinyl acetate copolymer are fully melted to form a continuous polymer melt;
[0060] The temperature in the mixing shear zone (sections four to six) is set between 180°C and 200°C. The screw configuration here is specially designed, typically incorporating a rational combination of multiple kneading blocks, mixing discs, and reverse conveying sections to provide extremely high shear forces and repeated stretching, compression, and folding. These high shear forces effectively break up the agglomerates of conductive carbon black, dispersing them uniformly in the polymer melt as nano-sized particles. Simultaneously, under this high-temperature and high-shear environment, the maleic anhydride groups of the maleic anhydride-grafted polyolefin can undergo a full in-situ chemical reaction with the functional groups on the surface of the surface-modified conductive carbon black, forming strong chemical bonds. This stabilizes the dispersion of the conductive carbon black at the molecular level, inhibiting its re-agglomeration.
[0061] The temperature of the metering zone (sections 7 and 8) is set to 170°C to 190°C, mainly for stabilizing melt pressure and metering delivery;
[0062] The die temperature is set to 170°C to 190°C to ensure that the extrudate has good surface quality and stable geometry.
[0063] Furthermore, peroxide crosslinking agents and functionalized silane coupling agents are temperature-sensitive. To prevent premature decomposition or unnecessary early crosslinking in the main mixing zone, they are typically added via the extruder-side feed port in a lower temperature zone, such as after the melting zone and before the metering zone. This stepwise addition strategy ensures that these active components can exert their maximum effectiveness in the subsequent crosslinking and curing process. The extruder's vacuum vent (usually located after the melting zone) can be used to remove any volatile substances that may be present in the melt, improving the material's density and electrical properties.
[0064] S4: Cooling and Granulation. The molten blend is extruded through a die to form uniform strands. These strands are then rapidly cooled using a water bath or air-cooling system. Rapid cooling helps to fix the molecular structure of the polymer and the dispersion of the conductive carbon black. The cooled strands are fed into a pelletizer to cut into granules of uniform size and shape. Granule uniformity is crucial for subsequent high-voltage cable extrusion molding, ensuring stable feeding and continuous production. The final granules are sampled and tested, including melt flow rate, ash content, and volume resistivity, to ensure product quality meets requirements.
[0065] Based on the above, this invention is demonstrated through experiments. First, an experimental group was conducted, and the conductive shielding material formulation for the experimental group is as follows (by weight):
[0066] Main polyolefin resin: 60 parts (of which, low-density polyethylene, density 0.920 g / cm³) 3 MFR 2.0 g / 10 min accounts for 40 parts; linear low-density polyethylene, density 0.918 g / cm³ 3(MFR 1.5g / 10min, 20 portions);
[0067] Ethylene-vinyl acetate copolymer: 20 parts (vinyl acetate content 22%);
[0068] Maleic anhydride-grafted polyethylene: 10 parts (maleic anhydride grafting rate 1.0%);
[0069] Surface-modified conductive carbon black: 30 parts (high-structure conductive carbon black, DBP absorption value 180mL / 100g, surface treated with plasma oxidation to introduce carboxyl and hydroxyl functional groups, particle size distribution 25-50nm);
[0070] Peroxide crosslinking agent: 1.0 part (dicumyl peroxide DCP);
[0071] Functionalized silane coupling agent: 1.5 parts (γ-aminopropyltriethoxysilane APTES);
[0072] Processing aid: 0.5 parts (zinc stearate);
[0073] Antioxidant: 0.3 parts (IRGANOX 1010 is selected).
[0074] The preparation method is as follows:
[0075] Step 1: Preparation of surface-modified conductive carbon black. High-structure conductive carbon black was placed in a plasma reactor and treated for 30 minutes under an oxygen atmosphere with 200W of radio frequency power. XPS analysis of the treated carbon black showed a significant increase in the content of oxygen-containing functional groups (such as carboxyl and hydroxyl groups) on its surface.
[0076] Step 2: Premixing. Accurately weigh 60 parts of the main polyolefin resin (40 parts of low-density polyethylene, 20 parts of linear low-density polyethylene), 20 parts of ethylene-vinyl acetate copolymer, 10 parts of maleic anhydride-grafted polyethylene, 30 parts of surface-modified conductive carbon black, 0.5 parts of zinc stearate, and 0.3 parts of IRGANOX 1010, and add them to a high-speed mixer. Mix at 1200 rpm for 10 minutes to ensure uniform dispersion of the materials, and the material temperature should not exceed 70°C during the mixing process.
[0077] Step 3: Melt blending. The premixed material is fed into a twin-screw extruder with an L / D ratio of 44 via a metering feeder. The screw speed is set to 250 rpm. The temperatures of each section of the extruder are set as follows: feed zone 150℃, melt zone 170℃, mixing and shearing zone 190℃, metering zone 180℃, and die 180℃. Peroxide crosslinking agent DCP (1.0 part) and functionalized silane coupling agent APTES (1.5 part) are added before the metering zone via a side feed port. In the mixing and shearing zone, the screw uses a combination of dense kneading blocks and mixing discs to provide high shear force, promoting the deagglomeration of carbon black and the in-situ reaction of maleic anhydride-grafted polyethylene with modified carbon black. The extruder is equipped with a vacuum exhaust port to remove volatile substances.
[0078] Cooling and granulation: The molten blend is extruded into strips through a die, cooled in a water bath, and then cut into uniform granules by a pelletizer.
[0079] Control group:
[0080] The conductive shielding material formulation of the control group was basically the same as that of the experimental group, but the step of surface-modified conductive carbon black was omitted. Unmodified high-structure conductive carbon black was used directly, and no functionalized silane coupling agent was added. Only peroxide was used for crosslinking.
[0081] The formula is as follows (by weight):
[0082] Main polyolefin resin: 60 parts (including low-density polyethylene LDPE, density 0.920 g / cm³) 3 MFR 2.0 g / 10 min accounts for 40 parts; linear low-density polyethylene (LLDPE) with a density of 0.918 g / cm³. 3 (MFR 1.5g / 10min, 20 portions);
[0083] Ethylene-vinyl acetate copolymer: 20 parts (VA content 22%);
[0084] Maleic anhydride-grafted polyethylene: 10 parts (maleic anhydride grafting rate 1.0%);
[0085] Conductive carbon black: 30 parts (high-structure conductive carbon black, DBP absorption value 180mL / 100g, no surface modification, particle size distribution 25-50nm);
[0086] Peroxide crosslinking agent: 1.0 part (dicumyl peroxide DCP);
[0087] Functionalized silane coupling agent: 0 parts;
[0088] Processing aid: 0.5 parts (zinc stearate);
[0089] Antioxidant: 0.3 parts (IRGANOX 1010).
[0090] The preparation method was similar to that of the experimental group, but unmodified conductive carbon black was used directly in step one, and functionalized silane coupling agent was not added from the side feed port in step three.
[0091] The experimental results are shown in the table below:
[0092]
[0093] Experimental results:
[0094] 1. The volume resistivity of the experimental group samples was significantly lower than that of the control group at both room temperature and high temperature. In particular, at a high temperature of 130℃, the volume resistivity of the experimental group was only 3.2 × 10⁻⁶. 2 The Ω·cm of the control group was 1.2 × 10⁻⁶. 3 The resistivity temperature rise ratio of the experimental group (130℃ / 23℃) was only 1.28 Ω·cm, lower than that of the control group (2.07). This proves that the present invention effectively suppresses the relative displacement of conductive carbon black and the destruction of conductive pathways at high temperatures through the in-situ chemical bonding of surface-modified conductive carbon black and maleic anhydride-grafted polyolefin and the double cross-linked network structure formed by peroxide / silane coupling agent, thereby ensuring the long-term stable conductivity of conductive shielding material under high temperature and high current carrying conditions.
[0095] 2. The experimental group achieved a tensile strength of 16.5 MPa and an elongation at break of 420%, which was better than the control group (tensile strength 13.8 MPa and elongation at break 350%), indicating that the double cross-linked network structure of the present invention can enhance the overall mechanical strength and toughness of the material.
[0096] 3. The peel strength of the experimental group reached 28.5 N / cm, which was higher than that of the control group (15.2 N / cm). This verifies the key role of maleic anhydride-grafted polyolefin as a reactive interfacial compatibilizer in enhancing the adhesion between the shielding layer and the insulation layer. Its polar maleic anhydride groups can form strong physical or chemical interactions with polar groups or residues in the insulation layer, thereby effectively preventing interfacial peeling and ensuring the reliability of the cable during long-term operation.
[0097] 4. The surface finish evaluation score of the experimental group was 4.8 points, which was better than the 3.0 points of the control group. This reflects that under the synergistic effect of surface-modified conductive carbon black and maleic anhydride grafted polyolefin, the conductive carbon black achieved ultra-fine and uniform dispersion in the polymer matrix, which greatly reduced the surface roughness defects caused by carbon black agglomerates.
[0098] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A conductive shielding material for high-voltage cables, characterized in that, By weight, it includes the following components: The composition includes 40 to 70 parts of a main polyolefin resin, 10 to 30 parts of an ethylene-vinyl acetate copolymer, 5 to 15 parts of maleic anhydride-grafted polyolefin, 20 to 40 parts of surface-modified conductive carbon black, 0.5 to 2 parts of a peroxide crosslinking agent, 0.5 to 3 parts of a functionalized silane coupling agent, 0.1 to 1 part of a processing aid, and 0.1 to 1 part of an antioxidant. The surface-modified conductive carbon black is a high-structure conductive carbon black that has undergone plasma oxidation treatment, solution graft polymerization and surface coupling agent pretreatment, with an oil absorption value of 150mL / 100g to 300mL / 100g and a particle size distribution of 20nm to 60nm. The peroxide crosslinking agent and the functionalized silane coupling agent form a dual crosslinking network structure, wherein the peroxide crosslinking agent initiates the formation of a three-dimensional organic polymer network in the polymer matrix, and the functionalized silane coupling agent forms an inorganic-organic hybrid siloxane network.
2. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The main polyolefin resin is low-density polyethylene, linear low-density polyethylene, or a mixture thereof in any proportion, with a density of 0.910 g / cm³. 3 Up to 0.930 g / cm 3 The melt flow rate (190℃ / 2.16kg) is 0.5g / 10min to 5g / 10min.
3. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The ethylene-vinyl acetate copolymer contains 18% to 28% vinyl acetate by mass.
4. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The maleic anhydride-grafted polyolefin is selected from maleic anhydride-grafted polyethylene or maleic anhydride-grafted linear low-density polyethylene, and the grafting rate of maleic anhydride is 0.5% to 2.0% by mass.
5. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The plasma oxidation treatment of the surface-modified conductive carbon black is carried out in a low-pressure gas environment, with the atmosphere being pure oxygen, air, or a mixture of nitrogen and oxygen in a volume ratio of 4:
1. The radio frequency power is 50W to 500W, and the treatment time is 10 minutes to 60 minutes. The solution graft polymerization involves grafting low molecular weight polyolefins onto the surface of the conductive carbon black under the action of a free radical initiator. The molecular weight of the low molecular weight polyolefin is 5000 to 10000 g / mol. The reaction temperature is 80℃ to 150℃, and the reaction time is 4 hours to 8 hours. The surface coupling agent pretreatment uses silane coupling agents or titanate coupling agents, reacting at 50℃ to 70℃ for 2 hours to 4 hours, followed by vacuum drying at 80℃ to 120℃ for 12 hours to 24 hours.
6. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The peroxide crosslinking agent is selected from one or more of dicumyl peroxide, di-tert-butyl peroxide, or 2,5-dimethyl-2,5-di-tert-butylperoxyhexane.
7. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The functionalized silane coupling agent is selected from one or more of vinyltrimethoxysilane, γ-aminopropyltriethoxysilane, or N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.
8. The conductive shielding material for high-voltage cables according to claim 1, characterized in that: The processing aid is selected from one or more of fatty acids and their derivatives, polyethylene wax or paraffin oil; the antioxidant is selected from one or more of hindered phenolic antioxidants, phosphite antioxidants or thioester antioxidants.
9. A method for preparing a conductive shielding material for high-voltage cables according to any one of claims 1-8, characterized in that, Includes the following steps: S1: Surface-modified conductive carbon black was prepared by plasma oxidation treatment, solution graft polymerization and surface coupling agent pretreatment to modify the high-structure conductive carbon black; S2: Premixing: The main polyolefin resin, ethylene-vinyl acetate copolymer, maleic anhydride grafted polyolefin, surface-modified conductive carbon black prepared in step S1, processing aids and antioxidants are added into a high-speed mixer in proportion and mixed at 500 rpm to 1500 rpm for 5 to 15 minutes, while controlling the temperature to ≤80°C. S3: Melt blending, the premixed material is fed into a twin-screw extruder with an aspect ratio of 36 to 52, the screw speed is 100 rpm to 300 rpm, and the temperatures of each section are: feed zone 140°C to 160°C, melt zone 160°C to 180°C, mixing and shearing zone 180°C to 200°C, metering zone 170°C to 190°C, and die zone 170°C to 190°C; the peroxide crosslinking agent and the functionalized silane coupling agent are added before the metering zone through the side feed port; S4: Cooling and granulation, extruding the molten blend into strips, cooling and then pelletizing.
10. A method for preparing a conductive shielding material for high-voltage cables according to claim 9, characterized in that: The S3 twin-screw extruder has a mixing and shearing zone equipped with a kneading block, a mixing disc, and a reverse conveying section to provide high shear force; the extruder is equipped with a vacuum exhaust port to remove volatile substances.
Citation Information
Patent Citations
A semiconductive shield cable material including surface-grafted modified carbon black
CN106566039A
Strippable cross-linking EVA (ethylene vinyl acetate) semi-conductive shielding material for power cables and preparation method of strippable cross-linking EVA semi-conductive shielding material
CN107129624A
Uniform, stable and breakdown-resistant high-voltage shielded cable
CN109608748A
Super-smooth high-voltage cable semi-conductive shielding material based on high-structure conductive carbon black and preparation method thereof
CN113956565A
High-voltage cable semi-conductive shielding material based on graphene oxide dispersed conductive carbon black and preparation method of high-voltage cable semi-conductive shielding material
CN115304854A
Cited By
Semi-conductive shielding material for high-voltage cable, preparation method of semi-conductive shielding material and high-voltage cable
CN121343273A
New energy copper alloy energy storage cable
CN121495236A